Despachos x escrachos : as representações sociais do encarceramento feminino - Martil, Daiana Maturano Dias (2018)
This study evaluates the factors involved in granting or denying home detention to women in pretrial detention at the Madre Pelletier Female State Prison (MPFSP), in Southern Brazil. The sampled responds to the requirements established in article 318 of the Brazilian Code of Criminal Procedure (BCCP), which recommends replacing pretrial detention with house arrest to the women who are pregnant or mothers of children under 12 years old. This research was based on two premises: (i) the enactment of Law 13.257/ 2016 known as the Legal Framework for Early Childhood - which promoted the change in the BCCP in order to meet the infants best interests - and (ii) the preparation of technical reports by MPFSP social and psychologist Assistants, later sent to the criminal process district, requesting an analysis to the house arrest granting. It was a mixed design study. Qualitative data were examined by the Discursive Textual Analysis theory, which is composed of three essential elements: unitarization, categorization and communication. Quantitative analysis encompass statistical calculations performed by Statical Package for the Social Scienses, version 21.0 for Windows. Furthermore, the sociodemographic profile of a total of 84 women was raised in the reports on the Justice Court website. From the analysis of the data, it was verified that 32% of the women had their request rejected. By refusing the house arrest the magistracy alleges the maintenance of public order to justify the non-granting for women in detention. However, the sample preponderance shows that the criminal imputation does not accompany violence acts. Homicide crimes accounted for only 7.1%, which shows that the majority of surveyed women in MPFSP could receive the house arrest grant. The interpretation of the discourses content reveals moralistic considerations referring to an idealized motherhood in the mold of the patriarchal culture, considering that these women are unfit for mothering precisely because they are accused of committing a crime. On the other hand, in the cases when house arrest was granting, it was evidenced by the judiciary the understanding of the indispensability of the maternal figure for the care of the children, thus protecting the best interest of the infant. Such findings may contribute to the elaboration of affirmative actions that subsidize the strengthening of house arrest concessions. Under the bastion of the Public Security Policy known as "Zero Tolerance", preventive detention could be understand as a social control tool of women who disregard the social role attributed to the feminine by the androcentric and patriarchal culture here represented by southern criminal justice system.